Work of a stroke team: experience of transferring ischemic stroke patients from district hospitals to Krasnoyarsk Regional Vascular Center for thrombectomy - P. G. Shniakin; N. V. Isaeva; V. Y. Kuznetsov; A. V. Protopopov; E. E. Korchagin; N. Y. Dovbish; N. V. Litvinyuk (Бюллетень сибирской медицины, 2022)
Modern high-technology methods for ischemic stroke treatment (systemic thrombolysis, mechanical thrombectomy, thrombaspiration, stenting of cerebral arteries) can improve the rehabilitation potential and survival of patients. Important tasks here are selection for reperfusion and its performance on the greatest possible number of peracute patients. Mechanical thrombectomy combined with systemic thrombolysis is the most effective reperfusion strategy in the therapeutic window, but the availability of endovascular methods is limited to highly specialized centres. One way to solve this problem is to organize effective logistics with stroke patients, which will provide high-tech care for patients living far from large treatment centers due to regulated interaction between institutions at different levels.The aim of the study was to improve emergency interaction related to transfer of peracute stroke patients from primary vascular units and district hospitals of the Krasnoyarsk region to Krasnoyarsk Regional Vascular Center for thrombectomy.